Penyusunan Rancangan Qanun Pengelolaan Satwa Liar di Aceh - Lestari, Rachmatika; Aulia, Eza; Ath-Thariq, Phoenna; Husna, Asmaul (Universitas Teuku Umar, 2020)
Human conflict with wildlife is a complex problem because it isn’t only related to human safety but also with the safety of wildlife itself. Conflicts that have occurred have pushed the Government of Aceh, District/City Government and related parties to be more wise in understanding the lives of wild animals so that the handling and prevention measures can be optimized and based on the root of the problem. For this reason, a legal protection is needed in the form of a qanun which is expected to be able to integrate all available resources to protect wildlife in Aceh. The method of implementation in community service is to get involved with the expert team Commission II DPRA in drafting the Qanun of Wildlife Management until finally the qanun was ratified on 27 September 2019 and then promulgated to be Qanun on 29 October 2019. The participation of the authors in the drafting of the draft qanun of wildlife includes part of the process of forming the qanun, including starting from the stages of planning, drafting, and discussion. While the stages of ratification or stipulation, enactment and dissemination are carried out by the DPRA and the Government of Aceh itself in accordance with their respective duties, functions and authorities.